2009
DOI: 10.1017/s1751731108002589
|View full text |Cite
|
Sign up to set email alerts
|

Differential adaptations during growth spurt and in young adult rat muscles

Abstract: During the post-weaning growth and maturation period (25/90 days after birth), rat limb muscles are submitted to specific adaptations. Our aim was to characterize the mechanical properties of two muscles that are opposite in terms of fibre-type distribution, the soleus and the extensor digitorum longus (EDL) muscles of male Wistar rats. Results showed a fast-to-slow fibretype transition in soleus while no modification in fibre-type distribution was observed in EDL. A growth-induced increase in muscle force was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 32 publications
1
6
0
1
Order By: Relevance
“…Summarizing the results of the age‐dependent studies, we did not identify studies that used the same animal and muscle types that were analyzed in the present study. However, quantitatively comparing these results with those obtained in previous experimental studies with rats (Lodder et al, ; Barros et al, ; Bénard et al, ) revealed similar relationships between the species during growth.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Summarizing the results of the age‐dependent studies, we did not identify studies that used the same animal and muscle types that were analyzed in the present study. However, quantitatively comparing these results with those obtained in previous experimental studies with rats (Lodder et al, ; Barros et al, ; Bénard et al, ) revealed similar relationships between the species during growth.…”
Section: Discussionsupporting
confidence: 82%
“…Age‐dependent measurements of morphometric and morphologic data during normal growth are rare. Independent of the degree of invasiveness, data have been collected from rats (high invasive) (Comer, ; De Koning et al, ; Heslinga and Huijing, ; de Haan et al, ; Tamaki and Uchiyama, ; Barros et al, ), rabbits (high invasive) (Crawford; 1950; Crawford, ; Alder et al, ; Crawford, ), and humans (non‐invasive) (Binzoni et al, ; Narici et al, ; Morse et al, ; O'Brien et al, ; Bénard et al, ; Yanagisawa et al, ; Weide et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, ; Barros et al . ). Pups from mothers submitted to protein malnutrition (7.8% protein) during lactation had delayed maturation of reflexes and a reduction in the time of exploration in the open field at 21 days of life (Barros et al .…”
Section: Introductionmentioning
confidence: 97%
“…Previous studies have shown that maternal malnutrition during pregnancy, lactation and early infancy can impair the development of brain structure and function, assessed as reduced cerebral vascularization and numbers of dendrites in rat offspring (Bennis-Taleb et al 1999;Barreto Medeiros et al 2002. Maternal low-protein diet during pregnancy and lactation results in disruption of the development of somatic features, ontogeny of reflexes and behaviour (Barreto Medeiros et al 2002Barros et al 2009). Pups from mothers submitted to protein malnutrition (7.8% protein) during lactation had delayed maturation of reflexes and a reduction in the time of exploration in the open field at 21 days of life (Barros et al 2006).…”
Section: Introductionmentioning
confidence: 99%